2023
DOI: 10.3390/ijms24043618
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation/Nutritional Status Scores Are Prognostic but Not Predictive in Metastatic Non-Small-Cell Lung Cancer Treated with First-Line Immune Checkpoint Inhibitors

Abstract: Biomarkers of systemic inflammation/nutritional status have been associated with outcomes in advanced-stage non-small-cell lung cancer (NSCLC) treated with immune checkpoint inhibitors (ICIs). However, most of them were not tested in cohorts of patients treated with ICIs in combination with chemotherapy (CT) (ICI+CT) or with CT alone, making it impossible to discriminate a predictive from a prognostic effect. We conducted a single-center retrospective study to search for associations between various baseline b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Recently, Mahiat et al [6] reported that systemic inflammatory/nutritional status was moderately associated with outcome after ICI monotherapy, ICI plus platinum-based chemotherapy, and chemotherapy alone in Caucasian patients with advanced NSCLC; for immunotherapy, it was prognostic but not predictive. Seban et al [7] identified high NLRs, PLRs, and SIIs as independent prognostic factors for first-line PD-1 blockade treatment of advanced NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Mahiat et al [6] reported that systemic inflammatory/nutritional status was moderately associated with outcome after ICI monotherapy, ICI plus platinum-based chemotherapy, and chemotherapy alone in Caucasian patients with advanced NSCLC; for immunotherapy, it was prognostic but not predictive. Seban et al [7] identified high NLRs, PLRs, and SIIs as independent prognostic factors for first-line PD-1 blockade treatment of advanced NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and biological data (e.g., total protein, albumin, and CRP levels; white blood cell, neutrophil, platelet, and lymphocyte counts; and height and weight) were extracted from the medical records and analyzed. Six indices reflecting systemic inflammatory and nutritional status based on previous studies [6] were calculated at baseline within 1 week of the first cycle of each treatment. The inflammatory indices were as follows: (1) NLR = neutrophil count/lymphocyte count [7], (2) PLR = platelet count/lymphocyte count [7], and (3) SII = platelet count × neutrophil count/lymphocyte count [7].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…explored systemic inflammation/nutritional status (including PNI) as predictive factors in 3 metastatic NSCLC cohorts treated in the first line by ICI monotherapy (n=75), ICI combined with chemotherapy (n=56), or chemotherapy alone (n=221). Their results supported that systemic inflammation/nutritional status could be associated with the outcomes independently of the treatment, and were therefore prognostic but not predictive ( 59 ). The ICI efficacy predicted by PNI also seemed independent of PD-L1 expression, since no association between PD-L1 TPS and PFS/OS was reported while a lower PNI was significantly associated with shorter PFS (HR: 1.704, p<0.05) ( 60 ).…”
Section: Non-tumoral Blood Cell Ratiosmentioning
confidence: 90%